The Policy on the Application of National Land Law and Its Influence on the Existence of Ulayat Rights of the Samin Tribe Indigenous People in the Karts Kendeng Mountains - Sulaiman, Nurcholis; Darmadi, Nanang Sri (TABELLIUS: Journal of Law, 2023)
This study aims to identify and analyze the problems of the existence of customary rights of the Samin tribal people against the policy of implementing national land law and their solutions. The approach method in this study is sociological juridical, with descriptive analytical research specifications. The data needed includes primary and secondary data, the data is collected by means of interviews and literature study, which are then analyzed using qualitative analysis. The research results show that the problem of the existence of customary rights of the Samin tribe in the karts kendeng mountains of Rembang is modernization and a change in the mindset of the indigenous people. Factors that influence these changes are internal factors in the form of changes from their indigenous peoples and external factors that are influenced by other cultures from outside. The samin community in the Rembang karts kendeng mountains is identical and has merged into an organic society in terms of social solidarity. With this change, the Samin people are no longer guided by their culture and customs and then become a society in general, so that customary rights which were formerly the rights of the Samin people are now individual rights, then PT Semen Indonesia uses them to build a factory in the area. The solution in particular is that the Samin community must care for, protect, preserve, manage, and utilize their Ulayat land so that their Ulayat land rights do not disappear. The general solution is that the government is expected to be able to realize legal certainty for indigenous peoples determine special legislation that thoroughly discusses customary rights.Keywords: Customary; Land; Society; Tribe.